IMPLEMENTING PROJECT-BASED LEARNING (PBL) IN ESP COURSES: REVIEW ON SYLLABUS DRAFT - Simbolon, Nurmala Elmin; Fitia, Tiara Nur (Language Circle: Journal of Language and Literature, 2023)
Adopting project-based learning (PBL) in English for Purposes (ESP) is believed to equip university graduates with  English skills effectively. The current Indonesian Education Ministry's Merdeka Belajar policy also highlights the importance of PBL in vocatipnal higher education. One challenge in implementing PBL in ESP courses is English teachers’ limited content knowledge. The research reported in this paper aims to draft and review  PBL-based ESP syllabi drafts at a government Polytechnic in Indonesia. The data set includes questionnaires from nine English lecturers and notes from focus group discussions (FGD) with three content lecturers and five English teachers. This study uses a descriptive approach using mixed data collection and analysis methods. Excel program analyzes questionnaire data and content thematic analysis to process qualitative data, namely the FGD transcript and drafts. The survey and FGD are used as the basis for the draft framework for the ESP syllabus design. The article ends with a critical review of the drafts.